The Implementation of the Reciprocal Teaching Strategy for Enhancing Listening Comprehension - Ahada, Ichi (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2023)
In order to demonstrate the value of reciprocal classroom strategies for improving students' listening abilities, this research examines the effectiveness of the approach by focuses on many modern pedagogic theories this strategy agrees with, demonstrating its efficacy as a technique that can be used in classrooms. Participating in this study were 78 students from Mulawarman University's English department. Three methods of data collection, tests, interviews, and observations have been used to gather the data. The numeric data were calculated using the ratter’s indicating the rating, and the qualitative data were examined using the constant comparative method. The study's findings showed that Reciprocal Teaching should succeed in overcoming beginners' difficulties with listening, keyword detection, identifying grammar and vocabulary, and differentiating remarkable sounds. The lectures are encouraged to implement the research's findings in order to help inheritor students learn to listen through reciprocal teaching. The enhancement of Reciprocal Teaching illustrated shape implies rating of pre-check became 43, increasing to first post-test 76.6 and second post-test 87.The goal of the study is to understand how much Reciprocal Teaching helps students overcome the obstacles to effective listening as well as the learning environment that results from its use. The importance of listening skills is discussed in the final section of the paper, along with how reciprocal teaching strategies can be used to develop students' higher-order thinking abilities and then engage them in meaningful conversations that will help them speak more effectively.